Thermal performance and economic analysis of solar photovoltaic water heater under the Malaysian climatic condition / Md. Shouquat Hossain - Md. Shouquat , Hossain (2012)

(untitled)
The solar energy is one of the highest reliable renewable energy resources. Solar water heater (SWH) system as a considerable application of solar energy has been studied by many researchers. There have been several innovations in the design of SWH through decades of research, and still there is a significant potential to improve the efficiency and optimize the cost of SWH through new and innovative designs. In this study, the modified design of the solar energy absorber of flat plate collector through a water heating system has achieved a commendable success experimentally. The Hottel- Whillier-Bliss equation and Annual Worth method were applied to determine the thermal performance and economic impact of the modified flat plate collector. The design of the sheet and tube was focused on this study. For designing these compartments the copper tube and aluminium sheet have been selected as the most appropriate materials. A solar PV panel was utilized to supply power for running the controller circuit and the water pump. The experiments were carried out for two months of June and July as the sunniest days in Malaysian climate. The results show the maximum water temperature of 45°C in the storage tank, have been obtained on a clear day operation. Similarly, this modified design of the solar water heater has achieved around 5% more thermal efficiency than the previous designs. The thermal efficiency has been found to decrease rapidly when the ambient temperature increases. The estimated thermal efficiency was 75% in the month June and 76% in the month July. The average daily collector heat loss in two months was 8.50 W/m2K (-13.05 W/m2C), which is considered a very low heat loss. Economically, the calculated payback period of the system is 5 years which is highly advantages for residential buildings.